Efficacy and safety of two-step acupuncture therapy for symptom relief in adults with mild to moderate ulcerative colitis: rationale and design of the TSA-UC randomised controlled trial - Weiming Wang; Zhishun Liu; He Chen; Shuai Gao; Sixing Liu; Hangyu Shi; Jiufei Fang; Ji-Zheng Ma; Xinyu Shen (BMJ Open)
Introduction Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD) characterised by episodes of symptoms including rectal bleeding, increased stool frequency and abdominal pain, impacting quality of life significantly. Conventional treatments often come with potential side effects and may not be sufficient. Acupuncture is increasingly recognised for its potential benefits in UC. This study aims to assess the efficacy and safety of acupuncture for symptom relief in mild to moderate UC.Methods and analysis This single-centre, parallel-arm, randomised, sham-controlled, the two-step acupuncture (TSA)-UC trial, will involve 64 adults with mild to moderate UC, randomly assigned in a 1:1 ratio to either the acupuncture or sham acupuncture group. Participants will receive 20 sessions of two-step acupuncture or sham acupuncture therapy over 8 weeks. Blinding will be applied to participants, outcome assessors and statisticians. The primary outcome measure is the change in Patient-Reported Outcome 2 (PRO2) from baseline at week 8. Secondary outcomes include changes from baseline in the following scales: PRO2 at other time points, weekly average Numeric Rating Scale (NRS) for bowel urgency, weekly average NRS for abdominal pain (both associated and not associated with bowel movement), the 32-item Inflammatory Bowel Disease Questionnaire, Work Productivity and Activity Impairment Questionnaire-IBD, Pittsburgh Sleep Quality Index and Hospital Anxiety and Depression Scale. The Patient Global Impression of Change will also be assessed. Long-term effects of acupuncture will be explored. Adverse events and additional treatments will be monitored throughout the study. The modified intention-to-treat population including participants who complete baseline assessments and receive at least one treatment session will be analysed.Ethics and dissemination The study has received ethical approval from the Ethics Committee of Guang’anmen Hospital, China Academy of Chinese Medical Sciences (2024-190-KY). The results will be published in a peer-reviewed medical journal.Trial registration number NCT06615765.